Progress in the search for blood substitutes, part 1 Preparations currently used in haemotherapy as an indicator of new drug development - Waldemar Grzegorzewski; Ewa Mil; Katarzyna Gołda; Anna Czarniecka-Kubicka; Łukasz Puchała (Polish Pharmaceutical Society, 2022)
The hospital pharmacy in polish conditions, rarely participates in the logistic process related to the transport, storage and administration of blood, however, it is involved in supplying the hospital with a variety of blood products and blood substitutes such as crystalloids, colloids and albumins. The awareness of logistic and technological problems, as well as the analysis of costs, legal and ethical restrictions related to the use of blood products, becomes essential for good, effective, merit-based cooperation between a clinical pharmacist and other health care specialists. Introducing a good blood substitute would solve the problem of donating blood, costly storage, transport and testing. Due to the specific nature of the blood administration procedure, it cannot be used in some situations for ethical and religious reasons. Current research in the search for blood substitutes does not focus on the exact reconstitution of blood with its cellular components. While it seems impossible to create a perfect preparation, products intended to partially replace the role of blood have a greater chance of being used. Examples include not only preparations for filling the vascular bed, but also a variety of oxygen carriers. It should be noted that the use of cell-free preparations solves numerous technological problems related to the use and administration of blood products. The lack of proteins in the product supporting the transport of oxygen and carbon dioxide in human tissues or medical equipment means no risk of allergic reactions, coagulation and the need to conduct tests before administration of the drug, which improves access to therapy by reducing technological problems, and increases the level of patient safety and allows you to improve the effectiveness of the therapeutic process. The series of articles will present the current state of the art, directions of research and development possibilities of blood products and blood substitutes, with particular reference to acellular oxygen transfer agents.